PKM DISEMINASI INFORMASI KESEHATAN BAHAYA PENYALAHGUNAAN NAPZA PADA REMAJA DI SMPN 16 KELAS 8 KOTA KUPANG PROVINSI NTT - Muntasir, Muntasir; Nur, Marselinus Laga; Wijaya, Pasifikus Christa (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Community Partnership Program for Dissemination of Health Information on Drug Use Hazards In adolescents, especially students of Kupang 16 Public Middle School in the form of lectures, simulations, demonstrations and visualization posters of Narcotics, Psychotropic and Addictive Substances. One of the problems The location was chosen as one of the locations of community service based on the results of field observations explaining the need for health dissemination at this school and there has never been any health dissemination activity involving public health faculty lecturers. Besides providing information and developments in health science and technology in handling health problems, including one of them to prevent drug abuse among adolescents, especially in junior high school students. This program method is to provide 1) planning and design of activities to be carried out. 2) supply of tool materials according to the planned requirements. 3) preparation for implementation. 4) implementation of activities. 5) banner installation and application tools. 6) Submission of material and drug socialization as a way to prevent drug abuse among adolescents. 7) frequently asked questions, suggestions, implementers and partners. 9) monitoring of activities by the FKM Undana monitoring team. 10) evaluation of Community Partnership Program activities by the activity implementing team and partners. 11) reporting the activities of the Community Partnership Program as the responsibility of the activities of the Community Partnership Program. This program output can provide added value knowledge and information. Specifically, this service activity is expected to be able to provide goals to direct the target (students of SMPN 16) for take precautionary measures against opportunities for health problems in adolescents, increase knowledge and understanding of adolescent health, pmpowering teenage students so that preventive actions can be implemented well, supporting government programs in maintaining and improving the health status of adolescents, identifying the dangers of drug abuse that can be experienced at adolescence, provide information and outreach about the dangers of drug abuse that can be experienced at adolescence, convey information and outreach about the sources or causes of the dangers of drug abuse, provide an understanding of the impact of the dangers of drug abuse on its growth and development in adolescence, provide solutions in the form of preventive measures and appropriate handling of the dangers of drug abuse that can occur in adolescence, and provide motivation to keep guarding against drug abuse that can occur at the age of adolescence.